2001
DOI: 10.1002/1521-4141(200112)31:12<3493::aid-immu3493>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel cluster of lectin-like receptor genes expressed in monocytic, dendritic and endothelial cells maps close to the NK receptor genes in the human NK gene complex

Abstract: The NK gene complex is a region on human chromosome 12 containing several families of lectin‐like genes including the CD94 and NKG2 NK receptor genes. We report here that the region telomeric of CD94 contains in addition to the LOX‐1 gene the novel human DECTIN‐1 and the CLEC‐1 and CLEC‐2 genes within about 100 kb. Sequence similarities and chromosomal arrangement suggest that these genes form a separate subfamily of lectin‐like genes within the NK gene complex. DECTIN‐1 is selectively expressed in dendritic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
91
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 35 publications
5
91
0
Order By: Relevance
“…It therefore seems unlikely that TLR4 is critical for signal perception of the yeast even more because siRNA against TLR4 failed to abolish Candida-induced CXCL8/IL-8 expression in ECs. According to our expression analysis (data not shown) and in line with an earlier report (47), dectin-1, the myeloid cell-expressed major receptor for fungal ␤-glucan, is not expressed by ECs thus excluding a role in Candidainduced endothelial signaling. Furthermore, the mannose receptor, another C-type lectin receptor, is absent in HUVEC (48).…”
Section: Discussionmentioning
confidence: 99%
“…It therefore seems unlikely that TLR4 is critical for signal perception of the yeast even more because siRNA against TLR4 failed to abolish Candida-induced CXCL8/IL-8 expression in ECs. According to our expression analysis (data not shown) and in line with an earlier report (47), dectin-1, the myeloid cell-expressed major receptor for fungal ␤-glucan, is not expressed by ECs thus excluding a role in Candidainduced endothelial signaling. Furthermore, the mannose receptor, another C-type lectin receptor, is absent in HUVEC (48).…”
Section: Discussionmentioning
confidence: 99%
“…Others and we have demonstrated that C-type lectinlike receptors are not restricted to NK cells, but are expressed by many other cell types including myeloid cells [8][9][10]. This introduces the novel concept that the myeloid paralogs of NK cell receptors might govern myeloid cell activation/inhibition in the same manner as those on NK cells.…”
Section: Introductionmentioning
confidence: 87%
“…The study of these activationand inhibitory NK cell receptorshas generated a number of interesting hypotheses, including immune privilege [1], the recognition of 'missing self', 'non-self' and 'induced self' [2][3][4][5], as well elucidating the underlying mechanisms of some of the immune responses to viruses [6] and malignancy [7]. Others and we have demonstrated that C-type lectinlike receptors are not restricted to NK cells, but are expressed by many other cell types including myeloid cells [8][9][10]. This introduces the novel concept that the myeloid paralogs of NK cell receptors might govern myeloid cell activation/inhibition in the same manner as those on NK cells.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Pharmacological activity of this compound was tested in several animal models in vitro and in vivo. In humans, in vitro experiments with fucoidan demonstrated several beneficial effects on ulcers and bleeding disorders (11,12). Non-anticoagulatory sulfated polysaccharides were originally considered as a novel approach to improve coagulation because of their inhibitory effect on physiological anticoagulation, especially fucoidan, which inhibits tissue factor pathway inhibitor and accelerates clotting in hemophilia A and B patients (8).…”
mentioning
confidence: 99%